A theory-based decision support framework for energy transition: pluralized perspective - Aasa, Olaoluwa Paul; Phoya, Sarah; Monko, Rehema Joseph; Musonda, Innocent (Frontiers in Sustainability, 2026)
This study presents a theory-based decision support framework for energy transitions that addressed the requirement for comprehensive approach beyond routine problem-solving techniques. The decision support framework integrates value-focused thinking, sustainability and resilience theories, and multi-criteria decision analysis (MCDA). The four theoretical lenses were synthesized to address three core support areas: alternatives identification, evaluation criteria development, and method selection. The resulting conceptual framework is structured into foundational, evaluation, and decision-making stages, each underpinned by stakeholder engagement and context alignment. To demonstrate usefulness, the article provides a detailed illustrative application to a hypothetical energy planning scenario in a Sub-Saharan Africa nation, an epicenter of energy access challenges. The framework offers transparency, adaptability, and rigor for methodological roadmap for national energy planning. This work provides a clear guide for policymakers and researchers to apply in diverse geographic and system scales, bridging the gap between theory and practical energy policy evaluation.